traits vascular plants - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Payne, Richard J.; Martí, Magalí; Bragazza, Luca; Bleeker, Albert; Buttler, Alexandre; Caporn, Simon J. M.; Dise, Nancy B.; Kattge, Jens; Zając, Katarzyna; Svensson, Bo H.; et al. (Dryad Digital Repository, 2017)
Plant functional traits used to calculate functional indices for the vascular plant communities. Traits were extracted from LEDA (Kleyer, M. et al. The LEDA Traitbase: a database of life‐history traits of the Northwest European flora. J. Ecol. 96, 1266–1274 (2008)). Only trait data available for all species our data-set were extracted.